Pengaruh Penerapan Kebijakan Pembelajaran Daring Terhadap Hasil Belajar Mahasiswa Di PG PAUD Universitas PGRI Argopuro Jember - Basuki Hadiprayogo (Universitas Muhammadiyah Ponorogo, 2023)
In the implementation of online learning policies during the Covid 19 pandemic at PGRI PAUD Universitas PGRI Argopuro Jember, when viewed from the existing obstacles, it will affect student learning outcomes at PG PAUD Universitas PGRI Argopuro Jember. The intended learning outcomes are the results obtained by students from the results of lecturer assessments in lecture activities in one semester. The research method used in this research uses a quantitative approach. This research is to measure and assess what effect the implementation of online learning policies has on student learning outcomes in the PG PAUD Undergraduate Study Program, PGRI Argopuro University, Jember. Researchers use observation sheets in data collection. The respondents in this study were 90 students consisting of semester 1 and semester 3 students of the PG PAUD Undergraduate Program at PGRI Argopuro University Jember. The results of the research analysis show that there is an influence on the application of online learning policies on student learning outcomes at PGRI PAUD University and PGRI Argopuro Jember. This was obtained because the sign value was between 0.01 and less than 0.05, so the online policy in this study had an effect on student learning outcomes. Meanwhile, the correlation/relationship value is 0.366, and from the results of this output, an R square of 0.127 is also obtained, which means that the influence of online learning policies is 12.7% on student learning outcomes.